Funkcjonowanie samorządu załóg przedsiębiorstw państwowych w okresie przezwyciężania kryzysu społeczno-gospodarczego - Sowiński, Roman (Wydział Prawa i Administracji UAM, 1985)
The author discusses in detail the posibilities of making use of the rights granted to workers of State enterprises in The State Enterprises Workers' Self- -government Act of 25 Sept. 1981 (Dziennik Ustaw Nr 24 sec. 123) and in The State Enterprises Act of 25 Sept. 1981 (Dziennik Ustaw Nr 24 sec. 122) in the situation of binding force of The Act of Special Legal Regulation in the Period of the Suspension of the State of Emergency of 18 Dec. 1982 (Dziennik Ustaw Nr 41 sec. 273) and later of The Act of the Special Legal Regulation in the Period of Overcoming the Socio-Economie Crisis of 21 July 1983. In the author's opinion the wording of the latter act became the source of numerous interpretational controversies questioning thus a possibility of the explicit decoding of the legislator's will. The doubts are particularly concerning the employed term of "dissolution of workers' self-government organ". The author studied in turn particular elements of the procedure of suspending activities of enterprise's workers' self-government organs, defined in the Act of 21 July 1983 (art. 9 sec. 2). That provision is to have a particular impact for the workers of the enterprise in case of its possible application. In the context of present conditions of self-government functioning, in the author's opinion it is not only procedure of decision making concerning the self-government organ which is essential but also a problem of responsibility for making the decision. Consequently, the author focuses on the problem of a legal character of the Commission for Workers' Self-Government which is to act on the base of the Act of 21 July 1983 by the Council of State. The present regulation is not precising the character of the above comimdssion and the interrelations between such commissions acting by the Seym, the Council of State and by the people's councils. Clarification of those issues would effect establishing the possible appeal procedures from the decision of „dissolution" the self-government organ, of "suspending" its activities and of "resumption" of its activities after the period of suspension.
Functioning of workers' self government in State enterprises in the period of overcoming the socio-economic crisis